Peasant Perceptions of Landscape. Ewelme Hundred, South Oxfordshire, 500–165 - Stone, David (Medieval Settlement Research, 2023)
In recent decades, peasants have gradually emerged from the historical shadows to take their place in the forefront of our perceptions of the past – a growing visibility that has been accompanied by an increased emphasis on mentalities. This word, or at least its French equivalent, is firmly associated with Emmanual Le Roy Ladurie, notably his inspirational study of Montaillou, a work showcased in the introduction to Mileson and Brookes’ engaging book on Ewelme Hundred. Together with Susan Kilby’s publications, peasants’ engagement with, and sense of, their surroundings has become a key feature of recent research. These refreshing evocations of landscapes and their meaning reflect the richness of the archaeological and documentary record and the meticulous yet innovative ways in which these forms of evidence are being analysed and combined.